J09 When do voice changes affect quality of life in Huntington's disease?. (16th November 2010) - Ho, A K; Cull, J; Drake, K; Barker, R A; Tabrizi, S J; Lee, P
Abstract : Background: Changes in the articulation of speech and in voice function (dysarthria) are known to be affected particularly in the latter stages of Huntington's disease, and are seldom investigated in the earlier on. Aims: This study investigated the impact of voice changes in patients at different stages of Huntington's disease severity. Methods: Forty one people with HD completed the Voice-Related Quality of Life questionnaire. These participants were at different disease stages, ranging from premanifest to the later stages of HD. This questionnaire assesses the participant's perception of their own quality of voice in speech and how they feel this influences their quality of life. Results: We found that participants report an early pattern of gradual decline in the total score of the voice-related quality of life measure, with a significant difference between Stage 4 and Stage 5 patients, and also between the premanifest and Stage 1 groups. Conclusions: The data show that people living with Huntington's disease reported that they felt the impact of changes in speech and voice very early on, as early as in Stage 1. The results also support the better recognised impact of Huntington's in voice and speech in the later stages of disease.